Gender, socioeconomic status, and time use of married and cohabiting parents during the Great Recession - Ebru Kongar; Mark Price (Levy Economics Institute of Bard College, 2017)
Using data from the 2003-14 American Time Use Survey (ATUS), this paper examines the relationship between the state unemployment rate and the time that opposite-sex couples with children spend on childcare activities, and how this varies by the socioeconomic status (SES), race, and ethnicity of the mothers and fathers. The time that mothers and fathers spend providing primary and secondary child caregiving, solo time with children, and any time spent as a family are considered. To explore the impact of macroeconomic conditions on the amount of time parents spend with children, the time-use data are combined with the state unemployment rate data from the US Bureau of Labor Statistics. The analysis finds that the time parents spend on child-caregiving activities or with their children varies with the unemployment rate in low-SES households, African-American households, and Hispanic households. Given that job losses were disproportionately high for workers with no college degree, African-Americans, and Hispanics during the Great Recession, the results suggest that the burden of household adjustment during the crisis fell disproportionately on the households most affected by the recession.
Keywords: D13; J16; J64; 330; Economics of Gender; Time Use; Economic Crises; Unpaid Labor